2014
DOI: 10.1016/j.trprot.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and magnetic (M2) proteomics of a mouse model of mild traumatic brain injury

Abstract: Short-term increases in oxidative stress and decreases in motor function, including debilitating effects on balance and motor control, can occur following primary mild traumatic brain injuries (mTBI). However, the long-term effects on motor unit impairment and integrity as well as the molecular mechanisms underlying secondary injuries are poorly understood. We hypothesized that changes in central nervous system-specific protein (CSP) expression might correlate to these long-term effects. To test our hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…The initial loss of body weight after TBI in wild type mice has been reported previously (Evans et al, 2014) and could be caused by decreased food and water intake as a result of nausea, and/or dizziness experienced after mild TBI (O’Neil et al, 2013). G93A mice characteristically lose body weight after disease onset as a result of reduced food intake and wasting of muscle tissue in the later stages of disease progression (Gurney et al, 1994).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The initial loss of body weight after TBI in wild type mice has been reported previously (Evans et al, 2014) and could be caused by decreased food and water intake as a result of nausea, and/or dizziness experienced after mild TBI (O’Neil et al, 2013). G93A mice characteristically lose body weight after disease onset as a result of reduced food intake and wasting of muscle tissue in the later stages of disease progression (Gurney et al, 1994).…”
Section: Discussionmentioning
confidence: 76%
“…EMG is used clinically to diagnose peripheral nerve injury and motor neuron diseases, such as ALS. Abnormal EMG findings were compiled as a score of denervation potentials per muscle group per limb in each animal as described previously (Evans et al, 2014). Linear regression showed a significant difference between the curves of EMG abnormalities for each treatment group [Linear Regression, p<0.001, F87.08 (6,69) n=5–7, Figure 4].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, CANB1 was then upregulated two weeks after TBI suggesting a post-acute neurotrophic function. Further support for TBI proteomic profiling can be found in a proteomic study by Evans et al where they identified an inverse temporal relationship between the loss of mature MBP and initiation of myelin-associated glycoprotein (MAG) over three month period after injury [39]. We further observed that MAG undergoes transient dephosphorylated at Y611 and Y620 between one and two weeks following TBI (2.8-fold relative to naïve control; p=8.3E-7, n=6 per group), two key L-MAG signaling motifs for initiating myelination [40].…”
Section: Time As Critical Factor In Tbi Proteomic Studiesmentioning
confidence: 99%